Structure and properties of MgB2 bulks: ab-initio simulations compared to experiment. Issue 1 (March 2020) - Romaka, V V; Prikhna, T A; Eisterer, M; Shapovalov, A P; Goldacker, W; Moshchil, V E; Kozyrev, A; Rindfleisch, M; Tompsic, M; Hellstrom, E E; Grechnev, G E; Zhang, V Sh; et al.
Abstract: Analysis of XRD patterns by Rietveld refinement has been shown that the main phase of superconducting MgB2 -based bulk materials (with high level of superconducting characteristics) has AlB2 type structure and near MgB1.8-1.68 O0.2-0.32 stoichiometry. The materials demonstrated the critical current densities up to 0.9 – 0.4 MA/cm 2 j c (at 0 - 1 T, 20 K); up to 15 T B c2 (at 22.5 K) and Birr (at 18 K). The ab-initio simulation confirmed (1) benefits in binding energy and enthalpy of formation if stoichiometry of the solid solution is near MgB1.75 O0.25 ; (2) energetic advantage in case if impurity oxygen present only in each second boron plane of MgB2 cell while the first boron plane of the same cell stays pristine and location of substituted oxygen atoms in the nearby positions. Besides, the results of ab-initio modeling allow explanation of the tendency towards segregation of O-impurity in MgB2 structure during synthesis or sintering, and formation of Mg-B-O inclusions or nanolayers (with MgO type of structure) which effect pinning. Calculated transition temperatures, Tc, for MgB1.75 O0.25 occurred to be 23.3 K, while for MgB2 it was 21.13 K only. Experimental Tc of the bulk materials was 35.7-38.2 K.